Pen and Key Holder Guns Three Cases - Yılmaz, Rıza; Birincioğlu, İsmail and Arslan, Ercan and Yolcu, Kirman and Bütün, Celal (The Bulletin of Legal Medicine, 2004)
After firearms have been started to be used extensively all around the world, they become important within the causes of deaths and injuries. Firearms are classified in two as short and long barrel firearms. In parallelity to technological advances, firearms with small dimensions are prefered since they are easy to carry, easy to use, easy to hide and difficult to determine. Pen and key holder guns mentioned in all over three cases are considered in the scope of act 6136. Key words: firearms, pen and key holder guns.